(untitled) (Journal of Humanitarian and Applied Sciences, 2020)
The main objectives of this paper were to study the performance and properties of beta particles by observing a β particle energy spectrum and to measure the range of a beam of beta particles emitted from the two given sources (90Sr and 60Co). This experiment was achieved by using two detectors which are the crystal of sodium iodide detector Nal(TI) and the Geiger Muller tube (G-M). The calibration of the Multi Channel Analyser (MCA) had been done using the known energies of the 22Na and 137Cs gamma rays. Furthermore, the spectra of β-particles were collected in order to determine both of the half- life time and the end-point energy of 128I, which found to be (23.1 minutes) and 2.19751 MeV respectively. In addition, both of the range and the half value thickness of beta particles were calculated by using different thicknesses of aluminium plates. And then, the measured values were compared to the calculated values that derived from the empirical equations which will be indicated in the theory section of this experiment.